Luteal Phase Support in IVF: Comparison Between Evidence-Based Medicine and Real-Life Practices - Di Guardo, Federica; Midassi, Habib; Racca, Annalisa; Tournaye, Herman; De Vos, Michel; Blockeel, Christophe (Frontiers in Endocrinology, 2020)
Background: Luteal phase support (LPS) in assisted reproduction cycles has been widely investigated in recent years. Although progesterone represents the preferential product for luteal phase supplementation in cycles with fresh embryo transfer, there is ongoing debate as to when to start, which is the best route, dosage and duration, and whether there is a place for additional agents. Nevertheless, fertility specialists do not always adhere to evidence-based recommendations in their clinical practice. The aim of this worldwide web-based survey is to document the currently used protocols for luteal phase support and appraisal tendencies of drug prescription behavior and to compare these to the existing evidence-based literature. Material and methods: A questionnaire was developed and sent by secure e-mail to 1480 clinicians involved in ART worldwide. 148 clinicians from 32 countries returned completed questionnaires. Results: Progesterone support is usually started on the day of oocyte retrieval. Eighty percent of clinicians applied the administration of vaginal progesterone only. Intramuscular progesterone was prescribed by 6%, while oral progestin or subcutaneous progesterone were each prescribed by 5% of clinicians, respectively. Progesterone was administered until 8-10 weeks’ gestation by 35% and 12 weeks by 52% of respondents. Conclusions: Vaginal administration was the preferred route for luteal phase support. The reported emerging use of the oral route confirms the expected shift in clinical practice as a result of recent evidence showing a reassuring safety score of oral progestins. In spite of the lack of evidence supporting the continuation of luteal support until 12 weeks’ gestation, this practice was adhered to by more than half of the clinicians surveyed, highlighting the difference between evidence-based medicine and real-life practices.